Occupational asthma caused by exposure to neurospora in a plywood factory worker. Issue 4 (April 1991) - Côté, J; Chan, H; Brochu, G; Chan-Yeung, M
Abstract : A 24 year old man developed severe asthma two years after starting to work in a plywood plant. Four years later the patient had to stop working because of the increasing severity of his asthma. Three months after leaving his job, the patient's asthma was greatly improved. His job consisted of placing plywood sheets into a drying machine. The plywood sheets had stayed outside in wet conditions for at least four to six weeks and were usually covered with moulds. Drying the plywood sheets changed the mould into a fine orange powder. Exposure to this in the laboratory induced an isolated immediate asthmatic reaction. The same reaction was seen when the patient was challenged with an extract of the mould powder at a 0.1% w/v concentration. Skin prick test with the mould extract induced a weal and flare reaction and IgE antibodies against the dry mould powder were identified. A control patient with the same degree of bronchial hyperreactivity did not have any asthmatic reaction when challenged with the same mould extract. Culture of the dry mould powder on Sabouraud agar plates grew pure Neurospora sp. This mould has not been previously reported as a cause of occupational asthma. The immunological mechanism is probably related to an IgE mediated mast cell allergy.